Inquiry-based science teaching competence of primary school teachers: A Delphi study - Alake-Tuenter, Ester; Biemans, Harm J.A.; Tobi, Hilde; Mulder, Martin (Teaching and teacher education, 2013)
Earlier, extracted inquiry-based science teaching competency elements and domains from the international literature were compared to the United States' National Science Teaching Standards. The present Delphi study aimed to validate the findings for the Netherlands, where such standards are lacking. Experts (N=33) were asked about the importance of 23 identified competencies. They confirmed the importance; proposed to add one competency and to differentiate between novice and experienced teachers. They suggested that teachers be provided with opportunities to integrate competence development regarding science knowledge, attitude and teaching skills throughout their career. •A Delphi study validated the findings of an earlier literature study using experts.•The necessity of science teaching competencies was confirmed and refined.•Distinction was made between requirements for novice and experienced teachers.•Attitude toward science should be positive from pre-service level onwards.•Content knowledge and pedagogical content knowledge may grow through experience.